Diverse structures of manganese(II) complexes based on 3,5-pyrazoledicarboxylic acid from discrete molecules to polymers - Shi, Fa-Nian
Four manganese(II) coordination complexes based on 3,5-pyrazoledicarboxylic acid (H(3)pdc) that are formulated as Mn-2(H2O)(8)(Hpdc)(2)center dot 3H(2)O, 1; Mn-4(H2O)(6)(Hpdc)(pdc)(2)center dot H2O, 2; Mn(H2O)(2)(Hpdc), 3 and Mn( H2O)( Hpdc), 4, respectively, have been synthesized as single crystal particles via hydrothermal reactions. 1 crystallizes in the orthorhombic space group Pbcn, which is packed as discrete molecules and further forms a 3 dimensional (3-D) supramolecular framework via comprehensive hydrogen bonding interactions; 2 is formed in the monoclinic, P2(1)/n space group, which features as infinite 2-D inorganic connectivity layers linked via hydrogen bonds among these layers into a 3-D supramolecular framework; 3 has the structure of monoclinic, P2( 1)/c, which can be viewed as infinite 1-D inorganic connectivity chains further generate a 3-D supramolecular framework via the hydrogen bonding around the chains; while 4 crystallizes in monoclinic P2(1)/n and is built into an open 3-D framework via the covalent bonds among nodes and pdc linkers. The photoluminescence of 2 and 3 are studied in room temperature. (C) 2013 Elsevier B. V. All rights reserved.